HISTORICAL OVERVIEW OF TRADITIONAL WEAVING OF UZBEKISTAN (World Bulletin of Social Sciences, 2023)
A loom in the history of mankind was one of the greatest inventions that met people's needs of vital items, such as fabrics for clothing and a variety of woven carpets for home insulation. In the process of historical development of society, skills in technology of weaving and in the device of looms were improved. As a result, woven products, which initially played exceptionally functional role, due to decorative pattern that was applied on it began to acquire an artistic appearance